If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
x+(2/3)*x-2/5 = 53/55 // - 53/55
x+(2/3)*x-2/5-(53/55) = 0
x+(2/3)*x-2/5-53/55 = 0
5/3*x-15/11 = 0 // + 15/11
5/3*x = 15/11 // : 5/3
x = 15/11/5/3
x = 9/11
x = 9/11
| -317/45=-4/5x+3x-4/9 | | -6x+6-4/7x=164/35 | | -9+5/6x+6/7x=-1724/231 | | 1/2x+1+3x=9/2 | | 6+1/2x+x=27/5 | | 5x-9+6x=-41/7 | | 5x+1/4-2/7x=9/14 | | x+5+1/4x=5 | | 4/5x+1+3x=214/5 | | 1/7x+9+6x=52 | | -58/21=2x+5/7x-1/2 | | 3x+2/7-7x=-166/7 | | 1/2-7x-3x=71/22 | | 5x-3/8+5/7x=2371/504 | | 4x+8/9+x=53/9 | | -2/7x+3-4x=143/21 | | -2/7x-10+x=-74/7 | | 4x+5+x=40 | | 2x+3/7+x=54/77 | | 5/7x+5/7-1/2x=46/77 | | 4x+7+2x=31 | | 7/8-1/3x+x=-11/24 | | -17/5=-1/5x+5x-1/5 | | 2/9-6x+5x=-16/9 | | 1/6x-1/3+6/7x=-13/168 | | -5x+5+4x=4 | | 9-4x+5/6x=-49/3 | | -2/7x+2+x=19/7 | | -223/6=-3x-3/4x+1/3 | | 5/6-5x+4x=-13/6 | | 1/6x+9+6x=100/7 | | 1/9-x+3x=217/9 |